The loess sequence of Dolní Věstonice, Czech Republic: a new OSL-based chronology of the Last Climatic Cycle - Fuchs, Markus; Kreutzer, Sebastian; Rousseau, Denis-Didier; Antoine, Pierre; Hatté, Christine; Lagroix, France; Moine, Olivier; Gauthier, Caroline; Svoboda, Jiri; Lisá, Lenka (Boreas, 2013)
The Dolní Věstonice loess section in the Czech Republic is well known for its high-resolution loess-palaeosol sequence of the last interglacial-glacial climatic cycle (Upper Pleistocene). The loess section is situated in a climatic transition zone between oceanic and continental climates and is therefore of great value in reconstructing past regional climate conditions and their interaction with climate systems, in particular that of the North Atlantic. Based on a combination of optically stimulated luminescence (OSL) ages, stratigraphic field observations and magnetic susceptibility measurements, a chrono-climatic interpretation of the Dolní Věstonice loess section is presented. To establish a reliable Upper Pleistocene chronology, a quartz OSL approach was applied for equivalent dose (De) determination. Monomineralic quartz extracts of three distinct grain sizes, fine (4-11 μm), middle (38-63 μm) and coarse (90-200 μm), were used and compared. Within error limits, the calculated OSL ages are the same for the different grain sizes, and the OSL ages are in stratigraphic order. The established OSL chronology is in agreement with a Weichselian litho- and pedostratigraphy. The Dolní Věstonice loess section is characterized by four pedosedimentary subsequences. At the base of the profile, subsequence I is characterized by a distinct Early Glacial soil complex, OSL-dated to c. 110 to 70 ka, representing one of the most complete records of environmental change in the European loess belt. Subsequence II is allocated to the Lower Pleniglacial and is characterized by laminated sandy loess. Middle Pleniglacial subsequence III is represented by a brown soil complex, and is followed by the uppermost subsequence IV, characterized by a thick body of laminated sandy loess, indicating strong wind activity and a high sedimentation rate of more than ∼1 mm a−1 during the Upper Pleniglacial. According to the OSL chronology, as well as to the sedimentological and palaeopedological investigations, it is likely that the sequence at Dolní Věstonice has recorded most of the climatic events expressed in the NGRIP δ18O reference record between 110 and 70 ka.